Coal Miners and the Longue Durée: Learning from Decazeville - McKay, Ian (Labour / Le Travail, 1987)
The article reviews and comments on "The Miners of Decazeville: A Genealogy of Deindustrialization," by Donald Reid.

The Lanarkshire Miners: A Social History of their Trade Unions, 1775-1874 - McKay, Ian (Labour / Le Travail, 1985)
This article reviews the book "The Lanarkshire Miners: A Social History of Their Trade Unions, 1775-1874," by Alan B. Campbell.
Keywords: CAMPBELL, Alan B.; LANARKSHIRE Miners: A Social History of Their Trade Unions 1775-1874, The (Book); Labor Unions; Nonfiction; REVIEWS; books

"By Wisdom, Wile or War:" The Provincial Workmen's Association and the Struggle for Working-Class Independence in Nova Scotia, 1879-97 - McKay, Ian (Labour / Le Travail, 1986)
Although the provincial Workmen's Association, founded in Springhill, Nova Scotia, in 1879, represented the greatest achievement of maritime workers in the nineteenth century, historians, guided by the records and recollections left by Robert Drummond and the union's demise in the massive strikes of 1909-11, have generally considered it as a highly conservative union, wedded to a conciliatory approach to management and reluctant to use the strike weapon. This article suggests, in contrast, that the PWA was never personified by Drummond and that the union was a remarkably decentralized body. Until 1885 it was a loose federation of craft lodges; from 1886 to 1890 it was a slightly more unified quasi-independent political and industrial movement; and from 1891 to 1897 it was a movement split between highly militant mainland lodges and more accommodating lodges in Cape Breton. This diversity within the union not only meant that highly militant and relatively quiescent lodges coexisted within it, but that there were equally striking ideological tensions, within both the "official philosophy" of the union as enunciated by Drummond, and within the "vernacular philosophy" of the rank and file. An overemphasis on Drummond's vision of "class harmony" has led historians to slight his zeal for radical democratic change and working-class independence; a corresponding preoccupation with the sources composed by Drummond — virtually all the sources usually cited in studies of the union — has obscured the less articulate, less developed, and far more important "vernacular" outlook of the rank-and-file miners, who fought tenaciously and even violently for working-class independence. Moreover, static appraisals of these tendencies at both the upper and lower levels of the union miss crucial shifts within them over time: a shift from a heavily-qualified paternalism to an explicitly political critique of industrial and political autocracy in the mid-1880s, and a shift to a drastic polarization between progressive militants and Liberal Party traditionalists in the mid-1890s. Except for the period 1895-7, in which the leadership was coopted by the Liberal Party, the PWA on both its upper and lower levels was serious about its pursuit of working-class political independence, and its lobbying achieved a record of political and social reforms unparalleled in nineteenth-century Canada. As a participant in some of Canada's largest nineteenth-century labour wars, and as an important force for the winning of working-class political rights, the PWA deserves to be remembered as one of the most successful and militant social movements in the maritime provinces.

Underdevelopment and Social Movements in Atlantic Canada - McKay, Ian (Labour / Le Travail, 1982)
This article reviews the book, "Underdevelopment and Social Movements in Atlantic Canada," edited by Robert Brym and R. James Sacouman.

Historians, Anthropology, and the Concept of Culture - McKay, Ian (Labour / Le Travail, 1981)
Although Marxist social historians have proclaimed that anthropology provides an analytical framework for modem social history, they have not specified which specific schools of anthropology should be sustained nor which anthropological theories have been validated by historical investigation. Contemporary debates in anthropology and historical anthropology reveal that historical materialism and anthropology use different methods of abstraction and that any marriage of anthropology and historical materialism will produce only conceptual confusion unless these basic differences are taken into account. The problem is seen in its most acute form in the uncritical adoption by social historians of the concept of "culture," which has brought contemporary social history to a theoretical impasse.

'An Impartial Umpire': Industrial Relations and the Canadian State, 1900-1911 - McKay, Ian (Labour / Le Travail, 1981)
This article reviews the book, "'An Impartial Umpire': Industrial Relations and the Canadian State, 1900-1911," by Paul Craven.

The Realm of Uncertainty: The Experience of Work in the Cumberland Coal Mines, 1873-1927 - McKay, Ian (Acadiensis, 1986)
...This article explores the mentality of the coal miners in the two distinct coalfields of Cumberland county from 1873 to 1927, the period in which they flourished within industrial capitalism. ...[It] does not attempt a full description of the intricate social history of these coalfields, nor to analyze their remarkable legacies of labour activism and workers' control. It focuses, instead, on the coal miners' underlying outlook. It seeks first to establish the basic structures of coal mining and suggest the strategic implications of these structures for coal miners. It then documents the emergence of a distinctive mining outlook, first by looking at the theme of the collective traditions of pit boys, and then by analyzing the outlook of independence of the colliers. It finally explores the ramifications of this mining outlook for society, taking as its theme the impact of pit deaths on the community. Its focus is on the "elementary forms of mining life", and this emphasis may allow us to come away from the study of one small group of coal miners with new questions for regional coal-mining history. --From author's introduction

Strikes in the Maritimes, 1901-1914 - McKay, Ian (Acadiensis, 1983)
Recent studies have illustrated the strength and significance of working-class movements in the Maritimes during the late 19th and early 20th centuries. Other work has emphasized the organization of local and international unions and the emergence of the socialist movement in the region. A study of strikes in the Maritimes can help provide a regional context for such work, and also help correct the regional imbalance in national historiography. Strikes themselves were crucial events, and no historical interpretation of the region in this period can safely overlook them. By studying the vigorous response of the region's workers to the new political economy of the early 20th century, we can start to understand the human implications of economic change. For these reasons, it is worth our effort to describe and analyze the general pattern of strikes, often in quantitative terms. This general pattern can then be related to the region's economic structure and help broaden our understanding of the economic revolution which transformed the region from the 1880s to the 1920s. In particular, two major themes emerge from this analysis: the transformation of the labour market and the revolution in the workplace. --From author's introduction

The Character of Class Struggle: Essays in Canadian Working-Class History, 1850-1985 - Palmer, Bryan D.; McKay, Ian; Heron, Craig; Maroney, Heather Jon; Webber, Jeremy; Brandt, Gail Cuthbert; Kealey, Gregory S. (Canadian social history series, 1986)
These essays introduce readers to the changing and complex character of class struggle in Canada. Individual essays focus on specific features of Canadian class struggle: regional differences, the role of gender, the character of trade union leadership to the specific nature of conflict in particular industries; and the general features of national periods of upheaval such as the year 1919 and the World War II period. [Of the eight essays, two are original to the volume, while the others are abridged or revised versions of articles that previously appeared in publications such as Labour/Le Travail and New Left Review.] --Publisher's description
Keywords: 19th century; 20th century; Canada; History; Labor disputes; Social conflict; Working class